Clonmel, Sedgwick County - Barnes, Matthew (Kansas State University, The Chapman Center for Rural Studies, 2017)
This study examines the town of Clonmel, in Illinois Township, Sedgwick County, Kansas. It lasted from 1871 to 1938. When the railway left accompanied by the rise of the automobile, Clonmel lost residents, but the bond of St. John’s Catholic Church has kept the town alive. This study relies on church history, newspaper articles, and site studies.
Matthew Barnes, “Clonmel, Sedgwick County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/196.
Keywords: Sedgwick County; Illinois Township; Catholic Mission; Catholic; Irish; Tornado